المُترجمات العربية في مجال تعليميات اللغات قراءة وصفية نقدية - هباشي, لطيفة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه المقالة إلى كشف مصادر الكتابة التعليمياتية العربية المترجمة؛ أي تلك المؤلفات التي شكلت مادتها المعرفية معينا نهلت منه عديد الكتابات العربية جل أفكارها وتصوراتها، وكانت الموجه لها في اختيار المواضيع التي طرقتها والإشكاليات التي طرحتها. وقد أفضت هذه الدراسة إلى تسجيل أربعة مصادر تمثلت في: المصادر الأجنبية والتجارب الذاتية والمؤلفات العربية والمترجمات، هذه الأخيرة التي تم التركيز عليها نظرا لأهمية الفعل الترجمي في نقل المعارف من ثقافة إلى أخرى. خلصت الدراسة إلى جملة من النتائج من بينها التأكيد على دور المترجمات في تقديم تعليميات اللغات إلى القارئ العربي، وفاعليتها في التأسيس النظري وفي توجيه البحث في قضايا اللغة العربية. : This article aims at investigating the sources of translated Arabic works in the field of didactics, referring to works that have formed the cognitive material from which many Arabic writings drew their ideas and concepts. It also delves into the factors that influenced the selection of topics and questions addressed in these works. The study identifies four sources, including foreign sources, personal experiences, Arabic works, and translated works. The focus is on translated works, given the importance of translation in transferring knowledge from one culture to another. The study confirms the role of translated works in presenting languages didactics to the Arab reader and their effectiveness in establishing theoretical frameworks and guiding research in Arabic language issues. .
Article
Keywords: تعليميات اللغات؛ المترجمات؛ الكتابة التعليمياتية؛ تعليم اللغات؛ المصادر المعرفية.; Languages didactics, translated works, instructionwriting, languages teaching, cognitive sourcesal